Implementation of differentiated service delivery for paediatric HIV care and treatment: opportunities, challenges and experience from seven sub-Saharan African countries - Anna Grimsrud; Rebecca Abelman; Catharina Alons; Jeni Stockman; Ivan Teri; Maryanne Ombija; Christopher Makwindi; Justine Odionyi; Esther Tumbare; Barry Longwe; Mahoudo Bonou; Juma Songoro; et al. (Family Medicine and Community Health)
Differentiated service delivery (DSD) models for HIV often exclude children and adolescents. Given that children and adolescents have lower rates of HIV diagnosis, treatment and viral load suppression, there is a need to use DSD to meet the needs of children and adolescents living with HIV. This commentary reviews the concept of DSD, examines the application of DSD to the care of children and adolescents living with HIV, and describes national guidance on use of DSD for children and adolescents and implementation of DSD for HIV care and treatment in children and adolescents in Elizabeth Glaser Pediatric AIDS Foundation (EGPAF)–supported programmes in seven sub-Saharan countries between 2017 and 2019. Programme descriptions include eligibility criteria, location and frequency of care delivery, healthcare cadre delivering the care, as well as the number of EGPAF-supported facilities supporting each type of DSD model. A range of DSD models were identified. While facility-based models predominate, several countries support community-based models. Despite significant uptake of various DSD models for children and adolescents, there was variable coverage within countries and variability in age criteria for each model. While the recent uptake of DSD models for children and adolescents suggests feasibility, more can be done to optimise and extend the use of DSD models for children and adolescents living with HIV. Barriers to further DSD uptake are described and solutions proposed. DSD models for children and adolescents are a critical tool that can be optimised to improve the quality of HIV care and outcomes for children and adolescents.